304 Correlation of Preoperative Suzuki Stage, Postoperative Matsushima Grade, and Clinical Outcomes in Surgically Treated Pediatric Moyamoya. (April 2023) - Wilson, Christopher; Newman, Sharlé; Martinez, Mesha; Huh, Andrew; Avila, Stephen; Ducis, Katrina
Abstract : INTRODUCTION: Moyamoya disease and syndrome among pediatric patients is often treated with surgical revascularization. There is limited literature regarding associations between preoperative angiography, postoperative angiography, and clinical outcomes. METHODS: We report a case series of consecutive moyamoya disease (MMD) and moyamoya syndrome (MMS) pediatric patients who underwent pial synangiosis. Correlations between preoperative Suzuki stage, Matsushima grade at one year postoperatively, and pediatric modified Rankin score (mRS) were assessed using Speakman's Rank correlation testing. Factors associated with angiographic and clinical outcomes were analyzed using Fisher's Exact tests. RESULTS: 40 patients (60 hemispheres) were treated with median follow up 2.29 years. No significant correlation between preoperative Suzuki stage and postoperative Matsushima grade was identified overall. Suzuki stage two hemispheres developed less robust revascularization. Preoperative Suzuki stage was not associated with postoperative disability severity whereas a nonsignificant trend towards improved clinical outcomes was observed with better Matsushima grade. Poor angiographic revascularization was more frequent in MMS patients, Sickle Cell Disease (SCD) patients, patients with preoperative ivy sign, preoperative NIHSS ≥3, and preoperative symptom duration more than 6 months. Postoperative intracranial hemorrhage, reoperation, Suzuki stage ≥5, and postoperative ischemic stroke conferred more unfavorable clinical outcomes whereas Matsushima A and B revascularization and symptom duration <6 months were protective from unfavorable outcomes. CONCLUSIONS: Although Suzuki stage does not significantly correlate with Matsushima grade, the degree of revascularization according to Matsushima grade may be associated with clinical outcomes. Multiple factors associated with degree of revascularization and clinical outcomes are identified.